2022
DOI: 10.1038/s41387-021-00180-1
|View full text |Cite|
|
Sign up to set email alerts
|

Supportive treatment of vascular dysfunction in pediatric subjects with obesity: the OBELIX study

Abstract: Introduction Overweight or obese children develop abnormal endothelial cell dysfunction and arterial intima–media thickening with increased vasomotor tone and inflammation. Curcumin, resveratrol, zinc, magnesium, selenium, and vitamin D have shown beneficial effects on endothelial function. We test, among overweight and obese pediatric subjects, the effects on the endothelium of a combination of curcumin, resveratrol, zinc, magnesium, selenium, and vitamin D. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Delta flow difference at heat provocation test (DF-HPT) was significant at 6 months of treatment (78.5 [72.0-94.0] vs. 63.0 [53.0-78.0], respectively, treatment and control, p < 0.001). No differences were noted in the Hyperemic Area Under Curve (AUC) index [15]. These results appear to be promising in enhancing endothelial function in this subset of subjects, but it is well known that the technique used to evaluate the endothelial function is used only in research and it is not easy to assess the effect of the singular micronutrients in this combined supplementation.…”
Section: Micronutrient Supplementation On Cardiovascular Healthmentioning
confidence: 70%
See 1 more Smart Citation
“…Delta flow difference at heat provocation test (DF-HPT) was significant at 6 months of treatment (78.5 [72.0-94.0] vs. 63.0 [53.0-78.0], respectively, treatment and control, p < 0.001). No differences were noted in the Hyperemic Area Under Curve (AUC) index [15]. These results appear to be promising in enhancing endothelial function in this subset of subjects, but it is well known that the technique used to evaluate the endothelial function is used only in research and it is not easy to assess the effect of the singular micronutrients in this combined supplementation.…”
Section: Micronutrient Supplementation On Cardiovascular Healthmentioning
confidence: 70%
“…We can assess that after this lifestyle program microvascular reactivity endothelium-dependent increased only in the group with supplementation, reaching values comparable to that of controls, this suggesting the potential to attenuate microvascular dysfunction in this subgroup [14 && ]. Recently we tested, among a group of 48 subjects, who were randomized into two groups (treatment vs placebo) the effects on the endothelium of a combination of vitamin D (1000 UI per day) and other micronutrients (curcumin, resveratrol, zinc, magnesium and selenium) [15]. Endothelial function was assessed by means of a postocclusive release hyperemic test (PORH) and a heat provocation test, attended at 0, 3 and 6 months of treatment.…”
Section: Micronutrient Supplementation On Cardiovascular Healthmentioning
confidence: 99%
“…In another double-blind randomized crossover trial, RSV (150 mg/day, 34 days) could not reduce arterial inflammation as measured with 18F-fluorodeoxyglucose PET in subjects at risk of developing type 2 diabetes mellitus [ 117 ]. Unfortunately, although the beneficial effects of RSV on CAD patients with potential dyslipidemia (mentioned in the previous section) and pediatric obese subjects [ 118 ] had been reported in some studies, some clinical studies about the effects of RSV on NAFLD or obese subjects’ vascular function showed passive results. These studies indicated that RSV supplementation had no effect on the levels of plasm-soluble adhesion molecules, inflammatory markers, and biomarkers of endothelial function [ 119 , 120 , 121 ].…”
Section: Clinical Trials Of Rsv In the Treatment Of Vascular Metaboli...mentioning
confidence: 99%
“…4 It may also have a role to play in lowering the risk of developing cardiovascular diseases in overweight and obese pediatric subjects. 47 while improving biomarkers of oxidative stress and inflammation in conditions of obesity, and type 2 diabetes, 29 and nonalcoholic fatty liver disease, visceral fat, and abdominal obesity. 48,49 Safari et al 50 concur that available studies do tend to indicate that curcumin has beneficial impacts on various anthropometric indices, such as body weight and BMI, 17,51 even if disputed by some [eg.…”
Section: Resultsmentioning
confidence: 99%